Revised status of Oridryas Meyrick, 1938: new synonyms of Ypsolopha Latreille, 1796, and Ypsolopha parenthesella (Linnaeus, 1761 (Yponomeutoidea: Ypsolophidae) - Sohn, Jae-Cheon; Stᾰnescu, Mihai (Zootaxa, 2016)
The eminent entomologist Aristide Caradja (1861–1955) published between 1925 and 1939, on his own or jointly with Edward Meyrick, a series of taxonomic papers on Chinese microlepidoptera including the descriptions of 18 new species in Yponomeutidae (Hyponomeutidae of authors). Their type specimens are currently deposited in two institutions, the Natural History Museum in London (BMNH: formerly British Museum of Natural History), as previously incorporated in the Meyrick collection, and the “Grigore Antipa” National Museum of Natural History in Bucharest, Romania (MGAB), as incorporated in the Caradja collection. The BMNH specimens were examined and illustrated by Clarke (1965). The type specimens of Oridryas kept in MGAB have never been studied since the original descriptions.